PENGARUH MEDIA SCRAPBOOK TERHADAP HASIL BELAJAR PADA PEMBELAJARAN PPKn KELAS III SD NEGERI 125138 PEMATANGSIANTAR - Simanjuntak, Melvin; Esti Marlina Sirait; Veronika Lestari Simanjuntak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aimsto determine the effect of Scrapbook Media on Learning Outcomes in PPKn Learning for Class III of SD Negeri 125138 Pematangsiantar. The background of this study is the low learning outcomes are significant changes in students’ knowledg, skills, and attitudes after going through the learning process, which can be meansured by success in understanding and mastering learning materials.The research method used in this study is an experimental method with a one-group pretest-posttest design. The research sample consisted of 22 class III students. The results showed that scrapbook media had a significant effect on improving PPKn learningoutcomes. The average pretest value of 54,09 was ranked to 80,45in the posttest with the percentage of learning completion ranking and 13,63% to 86,36%. The results of the hypothesis test obtained a t –value of 8,717> 1 table 2,056 and a significance of 0,000 > 0,05, so that the altervative hypothesis (Ha) was accepted. The conclusion of this study is that the scrapbook media in this study is effective in improving the learning outcomes of PPKn students in grade III of SD Negeri 125138 Pematangsiantar.